RESULTS OF POSITIONAL AND PHOTOMETRIC MEASURE- MENTS OF METEOR TRAJECTORIES OBSERVED IN MYKOLAIV 2017-2018 - Kulichenko, M. O.; Shulga, O.; Gorbanev, Yu. M. (Одеські астрономічні публікації, 2019)
Regular meteor observation using TV CCD unintensified techniques was started in 2011 in RI «Mykolaiv astronomical observatory» (RI MAO). The method of meteor registration is based on using “track- and-stack” technique for obtaining frames with reference stars and online meteor detection software developed at RI NAO. The main accent of the research is made on precise astrometry and meteoroid orbits calculation. New observa- tional campaign with baselines 11.7 and 100 km was start- ed in 2017-2018 in collaboration with Astronomical Ob- servatory of the I.I. Mechnikov Odessa National Universi- ty. Eight telescopes with narrow field lens (f=50 mm, f/1.2) were installed in Mykolaiv and Odessa. More than 3000 single station meteors and 221 double station mete- ors were detected during 2017-2018. Uncertainties of me- teor trajectory and orbital parameters are calculated using Monte Carlo method. Catalog of meteor trajectory posi- tions and photometric parameters has created. Standard deviation of approximation of a meteoric trajectory in a large circle is (15-20)". Kinematic parameters of atmos- pheric meteoric trajectories and elements of heliocentric orbits for 3 meteors were calculated based on the results of television observations with cameras with a field of view <10° at a baseline distance 100 km. The average uncertainty of visible radiant estimation is in (0.3-0.7)º with baseline 100 km. The geocentric velocity estimation uncertainty is 0.5 km/s, elevation uncertainty is 50-150 m.